Peran Guru Akidah Akhlak Dalam Membangun Peserta Didik Yang Berakhlakul Karimah Di Era Society 5.0 - Annisa Suseno Putri; Masykur H. Mansyur; Neng Ulya (Peneliti.net, 2022)
The author examines how the teacher's role in building students who have good morals in an increasingly sophisticated and free era. This study departs from the author's anxiety about the moral state of students in the Era of Society 5.0 which is increasingly sophisticated and makes it easier for students to gain access to socialize with anyone. So that it is vulnerable for students to make deviations at school. Therefore the role of the teacher as an educator is very important in terms of building students who have good morals through preventive, curative and resresive actions. With these problems, the goal to be achieved in this study is to find out how the role of teachers in building students who have good morals in the Era of Society 5.0. This thesis belongs to the type of descriptive qualitative research, which describes the facts in the field correctly and authentically. This research uses library research or library research. The researcher's data collection technique will be carried out by exploring the data according to the discussion. Data were obtained from various books, literature, journals, articles, documents, as well as information from print media or other relevant electronic media regarding the role of teachers in building students who have good morals in the era of society 5.0.